2015
DOI: 10.1111/1753-0407.12305
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glucose and hemoglobin A1c for the detection of diabetes in Chinese adults

Abstract: Background The aim of the present study was to evaluate the performance of plasma glucose (PG) and HbA1c for the detection of diabetes in the general population in China. Methods A cross‐sectional analysis was conducted in a nationally representative sample of 98 658 Chinese adults aged ≥18 years. Fasting plasma glucose and HbA1c levels were measured in all participants after at least a 10‐h overnight fast. An oral glucose tolerance test (OGTT) was conducted among participants without a self‐reported history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…The newest national cross-sectional survey of diabetes in China has found that the combination of FPG and HbA1c could identify the diabetes of the most diabetic individuals (approximately 85%) identified by any of the three tests ( i.e. , FPG, OGTT, and HbA1c) [ 28 ]. However, these results have already adequately revealed that diabetes has become a major public health problem in the China; the prevention and control of diabetes need improvement, even in economically-advanced areas with much better medical and health service facilities and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The newest national cross-sectional survey of diabetes in China has found that the combination of FPG and HbA1c could identify the diabetes of the most diabetic individuals (approximately 85%) identified by any of the three tests ( i.e. , FPG, OGTT, and HbA1c) [ 28 ]. However, these results have already adequately revealed that diabetes has become a major public health problem in the China; the prevention and control of diabetes need improvement, even in economically-advanced areas with much better medical and health service facilities and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 16.8% of all cases of diabetes were detected by HbA1c alone, but not by FPG or 2‐h PPG. Levels of most cardiovascular risk factors, such as BMI, waist circumference, and cholesterol, were higher in diabetes identified by HbA1c alone than in diabetes diagnosed using glucose …”
Section: Comparison Of Hba1c and Glucose Measurements In The Diagnosimentioning
confidence: 89%
“…For the three glycemic indices of HbA1c, FPG, and 2‐h post‐load plasma glucose (PPG), each misses cases of diabetes identified by another. Results from a cross‐sectional survey conducted in a nationally representative sample of 98 658 Chinese adults demonstrated that HbA1c ≥6.5% could identify 4.57% of Chinese adults as having newly diagnosed diabetes, followed by FPG and 2‐h PPG at 4.52% and 3.50%, respectively . The overlap of the three glycemic indices in diagnosing diabetes was modest.…”
Section: Comparison Of Hba1c and Glucose Measurements In The Diagnosimentioning
confidence: 99%
See 2 more Smart Citations